2011
DOI: 10.1007/s10404-011-0904-4
|View full text |Cite
|
Sign up to set email alerts
|

Porous bead-based microfluidic assay: theory and confocal microscope imaging

Abstract: Functionalized, porous microbeads provide large surface area to volume ratios, allowing the capture of relatively large quantities of target molecules from complex solutions and, thus, facilitating high-sensitivity assays. While in recent years the interest in bead-based assays has been growing, only a few studies focus on mass transfer in the bead's interior and on the binding kinetics of functionalized, porous beads. In this study, streptavidin-coated, porous agarose beads are controllably positioned within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…These models agree well with confocal imaging. (Thompson and Bau 2012) Similarly, our group has shown, through simulations and experimental evidence, the preponderance of porous beads as highly sensitive sensing elements due to the existence of internal convection inside porous beads. (Chou et al 2012) These bead-based devices have shown potential as highly sensitive, robust sensing elements for rapid detection of biological agents.…”
Section: Introductionmentioning
confidence: 80%
“…These models agree well with confocal imaging. (Thompson and Bau 2012) Similarly, our group has shown, through simulations and experimental evidence, the preponderance of porous beads as highly sensitive sensing elements due to the existence of internal convection inside porous beads. (Chou et al 2012) These bead-based devices have shown potential as highly sensitive, robust sensing elements for rapid detection of biological agents.…”
Section: Introductionmentioning
confidence: 80%
“…Another method for constructing a microbead array/probe library in a microfluidic cell is to place the functionalized microbeads in shallow wells arrayed at the bottom of the channel, and then place the channel top on the microbead array. [37][38][39][40] The height of the channel is the same size as the microbead diameter, so that the channel top holds the microbeads in place. The binding rate in this geometry approaches the idealized case of an unobstructed microbead in the channel for all Pe, but the microbead array assembly is undertaken ex-situ, which is more demanding than the in-situ hydrodynamic entrapment studied here.…”
Section: The Effect Of the Trap On The Mass Transfermentioning
confidence: 99%
“…[34][35][36], the binding of target to microbeads captured in traps has received very limited attention. Bau et al [37][38][39][40] studied the geometry of microbeads sandwiched between the top surface of a flow channel and a shallow well at the bottom of the channel (the microbeads were preassembled in the shallow wells before closing the cell), and obtained solutions for the target concentration on the microbead surface as a function of the stream velocity and target-probe kinetic rate constants. These simulations represent approximately the idealized case of unobstructed microbeads.…”
Section: Introductionmentioning
confidence: 99%
“…Thompson et al developed a model in an attempt to understand the effects of analyte diffusion coefficient, flow rate, and capture probe density on the kinetics on bead surfaces [131]. Further, the combination of confocal microscopy and computational simulations helped to define the spatial and temporal distribution of bound biotinylated quantum dots on streptavidin-coated beads [132]. …”
Section: Porous Bead Sensorsmentioning
confidence: 99%